Early Challenges of Nascent Social Entrepreneurs. (5th June 2012) - Renko, Maija
Abstract : Social entrepreneurs are celebrated as transformational leaders whose accomplishments create opportunities for those less fortunate. However, little is known about the early stages of social enterprise development. This study focuses on how a nascent entrepreneur's prosocial motivation affects the progress in building a new venture. Results show that prosocial motivation decreases the likelihood of firm emergence within a 4‐year follow‐up period, and even more so when the product offering of the emerging venture is new to the markets. These findings are discussed in the light of previous research on prosocial motivation, social entrepreneurship, market novelty, and nascent entrepreneurship.